Utilização de ferramentas de apoio à tomada de decisão como suporte ao Planejamento Integrado de Recursos energéticos (PIR) : implicações e soluções para o Estado do Espírito Santo - Fiorot, Guilherme Marques (2016)
The approach of the Integrated Resource Planning (IRP) is one that considers options on both the supply and demand to meet the need of different energy resources, while seeking to minimize the resulting costs for businesses and society. This research sought to make use of tools to assist the decision maker in making the RIP for the energy sector of the Holy Spirit, taking into account existing problems to diversify the renewable state matrix and analyzing the best current practices in countries They stand out in this segment. Through a SWOT analysis is done asurvey of the opportunities that the RIP can offer in areas with proven potential energy, confronting them with the existing barriers to this process. Then, making use of relations of cause / effect / response, proposed mechanisms of action are discussed that may help the RIP approach to be employed usefully maneria in the state through agents and instruments presented on sites that have been identified to minimize the energy sector's problems, given that this approach has shown benefits noticeable in other parts of the country and abroad.